DETERMINAN INDIKATOR FINANSIAL DAN NON FINANSIAL DALAM ANALISIS KREDIT DI ERA BIG DATA (STUDI PADA P2P LENDING) - Putu Prima Wulandari; Nurlita Novianti; Aulia Fuad Rahman (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2021)
This study aims to predict and explain the effect of financial indicators on the credit score in the P2P Lending platform credit analysis and the effect of non-financial indicators on the credit score in the P2P Lending platform credit analysis. This research focuses on peer to peer lending transactions found on the fintech service